Strategies to Encourage the Acceleration of Circular Economic Practices Among Youth Play as Agent of Change - Maya Maria; Anisa Zahwa Akbara; Hubertina Karolina Ngarbingan; Ginta Ginting (International Journal of Applied Business and International Management, 2023)
The implementation of the Circular Economy (Reduce, Reuse, Recycle, Recovery, and Repair) in Indonesia is having difficulties, various problems still arise, especially related to readiness to change behavior patterns. Gap research from various sources indicates that building awareness from the end user aspect is important for more in-depth investigation, especially related to the motivators and obstacles to implementing a circular economy. As agents of change, the younger generation is one group concerned about implementing circular economy practices. The younger generation is the ideal basis for becoming agents of change who play the role of players as well as consumers of the future. This research is intended to investigate to what extent the role of the younger generation (attitudes, norms, intentions, behavior) can be a trigger factor for strengthening the role as agents of change (willingness to participate). This research involved 253 young people from various regions in Indonesia. Through SEM-LISREL analysis to test the modeling, several interesting things were found, namely: 1) intention and behavior are strong determinants of forming awareness to participate in becoming agents of change that support positive attitudes to implement circular economy practices, 2) there are indications the poor aspect of the norm to encourage agents of change. The findings can complete the research gap that changes the role of the younger generation to be accelerators of Circular Economy practices in the future.